Formation, characterization and mathematical modeling of the aerobic granular sludge - Ni, Bing-Jie.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Aerobic granular sludge technology will play an important role as an innovative technology alternative to the present activated sludge process in industrial and municipal wastewater treatment in the near future. Intended to fill the gaps in the studies of aerobic granular sludge, this thesis comprehensively investigates the formation, characterization and mathematical modeling of aerobic granular sludge, through integrating the process engineering tools and advanced molecular microbiology. The research results of this thesis contributed significantly to the advance of understanding and optimization of the bacterial granulation processes, the next generation of technology for cost-effective biological wastewater treatment. Dr. Bing-Jie Ni works at Advanced Water Management Centre (AWMC) of The University of Queensland, Australia.
Research questions and thesis overview -- Quantitative description of the sludge granulation process -- Autotrophic and heterotrophic growth in aerobic granular sludge -- Storage and growth processes in Aerobic granular sludge -- Formation processes of extracellular polymeric substances (EPS) -- Fractionating and determination of the soluble microbial products (SMP) -- Fate of the microbial products in aerobic granular sludge -- Microbial products formation in autotrophic granular sludge -- Granulation in a pilot-scale SBR for treatment of municipal wastewater -- Startup of the anammox process by seeding aerobic granular sludge.
Keywords: Environmental sciences; Waste disposal; Biotechnology; Environment; Waste Management/Waste Technology; Environmental Science and Engineering; Environmental Engineering/Biotechnology.; Math. Appl. in Environmental Science